Silicon-based negative electrode active material, secondary battery and electrical device

JP7934045B2Active Publication Date: 2026-10-13CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025532992
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2026-10-13
Estimated Expiration
2043-03-06

AI Technical Summary

Benefits of technology

【0024】 本願の1つ又は複数の実施形態は、以下の一つ又は複数の有益な效果を有する。 (1)K元素とP元素は予期以上の相乗作用を獲得し、両者が連携して獲得した技術効果は両者をそれぞれ使用する簡単な加算より顕著に優れている。 (2)シリコン系負極活物質は改善されたサイクル性能を有し、 (3)シリコン系負極活物質は改善されたレート性能を有し、 (4)シリコン系負極活物質は高いエネルギー密度を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007934045000002
    Figure 0007934045000002
  • Figure 0007934045000003
    Figure 0007934045000003
  • Figure 0007934045000004
    Figure 0007934045000004
Patent Text Reader

Abstract

The present application provides a silicon-based negative electrode active material that contains an alkaline earth metal element-containing silicate and also contains K and P elements.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application relates to the technology of batteries, and more particularly to silicon-based negative electrode active materials, secondary batteries, and electrical devices. [Background technology]

[0002] In recent years, as the range of applications for secondary batteries has expanded, they are being widely used in various fields such as energy storage systems for hydroelectric, thermal, wind, and solar power plants, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace.

[0003] Due to their high energy density, silicon-based materials are considered promising silicon-based negative electrode active materials for secondary batteries. As secondary batteries have undergone significant advancements, higher demands are being placed on their electrochemical performance and other aspects. Therefore, there is still a need for higher-performance silicon-based negative electrode active materials in this field. [Overview of the project]

[0004] In view of the above issues, this application provides a novel silicon-based negative electrode active material, a secondary battery, and an electrical device, which will be described below.

[0005] In the first aspect, the present application provides a silicon-based negative electrode active material that contains an alkaline earth metal element-containing silicate and simultaneously contains both K and P elements.

[0006] In the above embodiment, the silicon-based anode active material contains a combination of K and P elements, and this specific combination improves the cycle performance and rate performance of the silicon-based anode active material. The combination of K and P elements produces a synergistic effect beyond expectations, and the technical effect obtained by their combined action is significantly better than the simple addition of using each element separately. Although not limited to the following theory, the K element can create a silicate structure with oxygen-containing silicon-based materials, while avoiding rapid expansion of silicon crystal grains and mitigating volume expansion during the cycling process, thereby effectively improving cycle performance. The P element can effectively reduce the ion diffusion barrier and increase the diffusion coefficient in the bulk phase of lithium ions, which is advantageous in improving the rate performance of the battery. Therefore, by employing the silicon-based anode active material of the present invention, secondary batteries can achieve both high cycle performance and rate performance.

[0007] In some embodiments, the content of element K is greater than the content of element P. Within the above ratio range, elements K and P exhibit a synergistic effect greater than expected, significantly improving the cycle performance and rate performance of the silicon-based anode active material.

[0008] In some embodiments, the mass ratio of the K element to the P element is 7:1 or greater, and selectively between 9:1 and 15:1. In the above embodiments, the silicon-based anode active material has improved cycle performance and rate performance.

[0009] In some embodiments, the content of element K is 600 ppm or more, and selectively between 800 ppm and 1500 ppm. In the above embodiments, the silicon-based anode active material has improved cycle performance and rate performance.

[0010] In some embodiments, the content of element P is 500 ppm or less, and selectively between 50 ppm and 200 ppm. In the above embodiments, the silicon-based anode active material has improved cycle performance and rate performance.

[0011] In some embodiments, the volume average particle diameter D of the silicon-based negative electrode active material v 50 is 4 μm to 10 μm, optionally 5 μm to 8 μm. In the above embodiments, the silicon-based negative electrode active material has improved cycle performance and rate performance.

[0012] In some embodiments, the specific surface area of the silicon-based negative electrode active material is 6 m 2 / g or less, optionally 2 m 2 / g to 5 m 2 / g. In the above embodiments, the silicon-based negative electrode active material has improved cycle performance and rate performance.

[0013] In some embodiments, the powder volume resistivity of the silicon-based negative electrode active material under a pressure of 4 MPa is 6 Ω·cm or less, optionally 0.5 Ω·cm to 4.5 Ω·cm. In the above embodiments, the silicon-based negative electrode active material has improved cycle performance and rate performance.

[0014] In some embodiments, the press density of the silicon-based negative electrode active material under a pressure of 49000 N is 1.4 to 1.8 g / cm 3 , optionally 1.5 to 1.7 g / cm 3 . In the above embodiments, the silicon-based negative electrode active material has improved energy density.

[0015] In some embodiments, the alkaline earth metal element-containing silicate comprises a magnesium-containing silicate, and the half-peak width of the XRD diffraction peak of the magnesium-containing silicate is 0.65° or less, optionally 0.40° to 0.60°. In the above embodiments, the silicon-based negative electrode active material has improved cycle performance and rate performance.

[0016] In some embodiments, the alkaline earth metal element-containing silicate includes a magnesium-containing silicate, and the crystal grain size of the magnesium-containing silicate is 12 nm or larger, and selectively 13 nm to 20 nm. In the above embodiments, the silicon-based anode active material has improved cycle performance and rate performance.

[0017] In some embodiments, at least a portion of the surface of the silicon-based negative electrode active material is covered with a coating layer.

[0018] In the second aspect, the present application is: To provide a raw material containing Si element, O element, K element, P element and alkaline earth metal element, The vapor deposition method employs a method in which the raw material is heated to form vapor, and then the vapor is cooled to form a deposited material. The present invention provides a method for preparing a silicon-based negative electrode active material according to any one of the above items, comprising: pulverizing a deposited material and obtaining a pulverization product.

[0019] In some embodiments, the method for preparing silicon-based negative electrode active material is as follows: The process further includes applying a coating treatment to the pulverized product to obtain a product with a coated layer.

[0020] In some embodiments, the heating temperature in the operation of heating the raw material to form steam is 1100 to 1550°C.

[0021] In some embodiments, the cooling temperature in the operation of cooling the vapor to form a deposited material is 700 to 900°C.

[0022] In a third aspect, the present application provides a secondary battery including a negative electrode containing a silicon-based negative electrode active material as described in any one of the above paragraphs.

[0023] In a fourth aspect, the present application provides an electrical device including a secondary battery as described in any one of the above paragraphs. [Effects of the Invention]

[0024] One or more embodiments of the present application have one or more beneficial effects. (1) The K element and the P element have achieved a synergistic effect beyond expectations, and the technological effect obtained by their combined efforts is significantly superior to a simple addition using each element separately. (2) The silicon-based negative electrode active material has improved cycle performance, (3) The silicon-based negative electrode active material has improved rate performance, (4) Silicon-based negative electrode active materials have a high energy density. [Brief explanation of the drawing]

[0025] [Figure 1] This is a schematic diagram of a secondary battery according to one embodiment of the present invention. [Figure 2] Figure 1 is an exploded view of a secondary battery according to one embodiment of the present invention. [Figure 3] This is a schematic diagram of a battery module according to one embodiment of the present application. [Figure 4] This is a schematic diagram of a battery pack according to one embodiment of the present application. [Figure 5] Figure 4 is an exploded view of a battery pack according to one embodiment of the present invention. [Figure 6] This is a schematic diagram of an electrical device using a secondary battery as a power source according to one embodiment of the present invention. [Explanation of Symbols]

[0026] 1...Battery pack, 2...Upper casing, 3...Lower casing, 4...Battery module, 5...Rechargeable battery, 51...Housing, 52...Electrode assembly, 53...Top cover assembly. [Modes for carrying out the invention]

[0027] The following detailed description of the drawings specifically discloses the silicon-based negative electrode active material and its manufacturing method, positive electrode sheet, negative electrode sheet, secondary battery, battery module, battery pack, and apparatus embodiments of the present application, with due reference to the drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of the same structure may be omitted. This is to avoid making the following description unnecessarily long and to facilitate understanding for those skilled in the art. Furthermore, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0028] The “range” disclosed in this application is limited in the form of a lower limit and an upper limit, and a given range is limited by selecting one lower limit and one upper limit, and the boundaries of the special range are limited by the selected lower and upper limits. The range thus limited may include or exclude endpoint values, and may be in any combination, that is, any lower limit may be combined with any upper limit to form a single range. For example, if the ranges 60~120 and 80~110 are given for a particular parameter, it is understood that the ranges 60~110 and 80~120 are also expected. Also, if the minimum range values ​​1 and 2 are given, and the maximum range values ​​3, 4 and 5 are given, then the ranges 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 are all expected. In this application, unless otherwise specified, the numerical range “a~b” is an abbreviated expression for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0 to 5" in this paper indicates that all real numbers between "0 to 5" are listed, and "0 to 5" is merely an abbreviated representation of these numerical combinations. Furthermore, when expressing that a parameter is an integer greater than or equal to 2, it is equivalent to disclosing that the parameter is an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0029] Unless otherwise specified, all embodiments and preferred embodiments of this application may be combined to form new technical embodiments.

[0030] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, but it is preferable to perform them sequentially. For example, if the method includes steps (a) and (b), the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method mentioned above may further include step (c), and step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.

[0031] Unless otherwise specified, the terms "include" and "include" as used in this application may be open or closed. For example, the terms "include" and "include" may mean that other components not listed may be included or included, or that only the listed components may be included or included.

[0032] Unless otherwise specified, the term "or" in this application is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, any one of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist), A is false (or does not exist) and B is true (or exists), or both A and B are true (or exist).

[0033] In this paper, ppm (parts per million) refers to parts per million. However, when ppm is used to describe the content of K or P elements, it means the mass of K or P elements in the silicon-based anode active material as a percentage of the total mass of the silicon-based anode active material.

[0034] [Secondary battery] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be used again after being discharged by activating the active material through a charging method.

[0035] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charging and discharging process of the battery, active ions (e.g., sodium ions) reciprocate between the positive and negative electrode sheets, being inserted and removed. The separator is placed between the positive and negative electrode sheets and primarily serves to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through. The electrolyte is located between the positive and negative electrode sheets and primarily serves to conduct active ions.

[0036] A secondary battery is, for example, a lithium-ion battery. The components of a lithium-ion battery mainly consist of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive and negative electrodes are separated by a separator to prevent short circuits, and the electrolyte impregnates the positive and negative electrodes to ensure ion conduction. During charging, Li + Li+ ions detach from the positive electrode and are inserted into the negative electrode via the electrolyte and separator, thereby placing the positive electrode in a high-potential, sodium-deficient state and the negative electrode in a low-potential, sodium-rich state. The discharge process is the reverse: Li+ ions detach from the negative electrode and are inserted into the positive electrode material via the electrolyte and separator, thereby returning the positive electrode to a sodium-rich state. To maintain charge balance, the same number of electrons are transferred through an external circuit during the charging and discharging processes, moving between the positive and negative electrodes along with Li+ ions, causing oxidation and reduction reactions at the positive and negative electrodes, respectively. Lithium ions can move reversibly between the positive and negative electrodes in the electrolyte, and both the positive and negative electrodes are composed of insertion-type materials that allow for the reversible insertion and detachment of lithium ions.

[0037] A secondary battery is, for example, a sodium-ion battery. The components of a sodium-ion battery mainly consist of a positive electrode, a negative electrode, a separator, and an electrolyte. The positive and negative electrodes are separated by a separator to prevent short circuits, and the electrolyte impregnates the positive and negative electrodes to ensure ion conduction. During charging, Na +Na+ ions detach from the positive electrode and are inserted into the negative electrode via the electrolyte and separator, thereby placing the positive electrode in a high-potential, sodium-deficient state and the negative electrode in a low-potential, sodium-rich state. The discharge process is the reverse: Na+ ions detach from the negative electrode and are inserted into the positive electrode material via the electrolyte and separator, thereby returning the positive electrode to a sodium-rich state. To maintain charge balance, the same number of electrons are transferred through an external circuit during the charging and discharging processes, moving between the positive and negative electrodes along with Na+ ions, causing oxidation and reduction reactions at the positive and negative electrodes, respectively. Sodium ions can move reversibly between the positive and negative electrodes in the electrolyte, and both the positive and negative electrodes are composed of insertion-type materials that allow for the reversible insertion and detachment of sodium ions.

[0038] [Negative electrode sheet] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector, the negative electrode film layer containing a negative electrode active material.

[0039] The negative electrode active material of this application is a silicon-based negative electrode active material that contains an alkaline earth metal element-containing silicate and simultaneously contains both K and P elements.

[0040] In the above embodiment, the silicon-based anode active material contains a combination of K and P elements, and this specific combination improves the cycle performance and rate performance of the silicon-based anode active material. The combination of K and P elements produces a synergistic effect beyond expectations, and the technical effect obtained by their combined action is significantly better than the simple addition of using each element separately. Although not limited to the following theory, the K element can create a silicate structure with oxygen-containing silicon-based materials, effectively reducing lithium ion consumption and effectively improving cycle performance, while the P element can effectively reduce the ion diffusion barrier and increase the diffusion coefficient in the bulk phase of lithium ions, which is advantageous in improving the rate performance of the battery. Therefore, by adopting the silicon-based anode active material of the present invention, secondary batteries can achieve both high cycle performance and rate performance.

[0041] In some embodiments, the silicon in the silicon-based anode active material may exist in multiple silicon phases, including crystalline silicon. Specifically, the silicon phases may be uniformly distributed and embedded in the matrix containing the silicon-based anode active material. In other words, the silicon phases may be dispersed and uniformly distributed in the matrix.

[0042] In some embodiments, the alkaline earth metal element includes one or more of the elements Mg, Be, Ca, and Ba. In these embodiments, the silicon-based anode active material exhibits improved cycle performance and rate performance.

[0043] In some embodiments, the alkaline earth metal element includes the element Mg. In these embodiments, the silicon-based anode active material exhibits further improved cycle performance and rate performance.

[0044] In some embodiments, the alkaline earth metal element-containing silicate includes a magnesium-containing silicate, and the half-peak width of the XRD diffraction peak of the magnesium-containing silicate is 0.65° or less, and selectively between 0.40° and 0.60°. In the above embodiments, the silicon-based anode active material has further improved cycle performance and rate performance.

[0045] In some embodiments, the alkaline earth metal element-containing silicate includes a magnesium-containing silicate, and the crystal grain size of the magnesium-containing silicate is 12 nm or larger, and selectively 13 nm to 20 nm. In the above embodiments, the silicon-based anode active material has further improved cycle performance and rate performance.

[0046] In some embodiments, the silicon-based negative electrode active material contains at least one of silicon crystal grains and silicon material crystal grains.

[0047] In some embodiments, the K and P elements grow within the silicon-based anode active material, for example, during the process of vapor deposition of the silicon-based anode active material. In some embodiments, when the K and P elements are vapor-deposited together with the silicon-based anode active material, they grow within the silicon-based anode active material.

[0048] In some embodiments, the content of element K in the silicon-based anode active material is greater than the content of element P. Within the above ratio range, elements K and P exhibit a synergistic effect greater than expected, further significantly improving the cycle performance and rate performance of the silicon-based anode active material.

[0049] In some embodiments, the silicon-based anode active material has a K-to-P mass ratio of 7:1 or higher (e.g., 7.7:1) or higher. Within this ratio range, the K and P elements exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0050] In some embodiments, the silicon-based anode active material has a K-to-P mass ratio of 7:1 to 15:1 (e.g., 7.7:1 to 14.1:1). Within this ratio range, the K and P elements exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0051] In some embodiments, the silicon-based anode active material has a K to P mass ratio of 10:1 to 14:1 (e.g., 10.3:1 to 13.8:1). Within this ratio range, the K and P elements exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0052] In some embodiments, the silicon-based anode active material has a K to P mass ratio of 12:1 to 13:1. Within this ratio range, the K and P elements exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0053] In some embodiments, the mass ratio of K element to P element in the silicon-based anode active material may be 20:1 or less, 15:1 or less, 14:1 or less, 13:1 or less, or 12:1 or less. In some embodiments, the mass ratio of K element to P element in the silicon-based anode active material may be 2:1 or more, 3:1 or more, 4:1 or more, 5:1 or more, 6:1 or more, 7:1 or more, or 8:1 or more. The mass ratio of K element to P element may consist of any of the upper and lower limits mentioned above. Within the above ratio range, the K element and P element exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0054] In some embodiments, the mass ratio of element K to element P may be 13-14:1, selectively 12-14:1, selectively 11-14:1, selectively 10-14:1, selectively 9-14:1, selectively 9-15:1, selectively 8-15:1, selectively 7-15:1, selectively 6-15:1, selectively 5-15:1, selectively 4-15:1, selectively 3-15:1, selectively 2-15:1, and selectively 1-15:1.

[0055] In some embodiments, the content of element K in the silicon-based anode active material is 600 ppm or more. Within this content range, element K and element P exhibit a synergistic effect beyond expectations, significantly improving the cycle performance and rate performance of the anode active material.

[0056] In some embodiments, the content of element K in the silicon-based anode active material is between 800 ppm and 1500 ppm. Based on this, the anode active material exhibits further improved cycle performance and rate performance. Within the above content range, element K and element P exert a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0057] In some embodiments, the content of element K in the silicon-based anode active material is 1000 ppm to 1500 ppm. Based on this, the anode active material has further improved cycle performance and rate performance. Within the above content range, element K and element P exhibit a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0058] In some embodiments, the content of element K in the silicon-based anode active material is between 1100 ppm and 1400 ppm. Based on this, the anode active material exhibits further improved cycle performance and rate performance. Within the above content range, element K and element P exert a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0059] In some embodiments, the content of element K in the silicon-based anode active material is between 1100 ppm and 1300 ppm. Based on this, the anode active material exhibits further improved cycle performance and rate performance. Within the above content range, element K and element P exert a synergistic effect beyond expectations, further significantly improving the cycle performance and rate performance of the anode active material.

[0060] In some embodiments, the K element content in the silicon-based anode active material is 1200 ppm to 1300 ppm. Based on this, the anode active material exhibits further improved cycle performance and rate performance. Within the above content range, the K and P elements exert a synergistic effect beyond expectations, significantly improving the cycle performance and rate performance of the anode active material.

[0061] In some embodiments, the upper limit of the K element content in the silicon-based anode active material may be any one value selected from 1500 ppm, 1400 ppm, 1300 ppm, and 1200 ppm, and the lower limit of the K element content may be any one value selected from 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm, and 1100 ppm. In other words, the range of the K element content may consist of the aforementioned arbitrary upper and lower limit values. Within the above content range, the K element and the P element exhibit a synergistic effect greater than expected, significantly improving the cycle performance and rate performance of the anode active material.

[0062] In some embodiments, the content of element K in the silicon-based negative electrode active material is 1200-1300 ppm, selectively 1100-1300 ppm, selectively 1200-1400 ppm, selectively 1100-1400 ppm, selectively 1000-1400 ppm, selectively 1000-1500 ppm, and selectively 800-1500 ppm.

[0063] In some embodiments, the content of element P in the silicon-based anode active material is 500 ppm or less. Based on this, the anode active material has further improved cycle performance and rate performance.

[0064] In some embodiments, the content of element P in the silicon-based anode active material is between 50 ppm and 200 ppm. Based on this, the anode active material has further improved cycle performance and rate performance.

[0065] In some embodiments, the content of element P in the silicon-based anode active material is between 75 ppm and 150 ppm. Based on this, the anode active material has further improved cycle performance and rate performance.

[0066] In some embodiments, the content of P element in the silicon-based negative electrode active material is 75 ppm to 100 ppm. On this basis, the negative electrode active material has further improved cycle performance and rate performance.

[0067] In some embodiments, the content of P element in the silicon-based negative electrode active material is 80 ppm to 95 ppm. On this basis, the negative electrode active material has further improved cycle performance and rate performance.

[0068] In some embodiments, the upper limit of the content of P element in the silicon-based negative electrode active material may be any one value selected from 200 ppm, 190 ppm, 170 ppm, 150 ppm, and 130 ppm, and the lower limit of the content of the P element may be any one value selected from 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm, 80 ppm, 90 ppm, and 100 ppm, that is, the range of the content of the P element may consist of any of the aforementioned upper limit and lower limit values. Within the above content range, the K element and the P element exhibit a synergistic effect beyond expectation, which significantly improves the cycle performance and rate performance of the negative electrode active material.

[0069] In some embodiments, the content of P element in the silicon-based negative electrode active material is 90 to 100 ppm, optionally 80 to 100 ppm, optionally 80 to 110 ppm, optionally 80 to 120 ppm, optionally 70 to 120 ppm, optionally 70 to 130 ppm, optionally 70 to 140 ppm, optionally 70 to 150 ppm, optionally 70 to 160 ppm, optionally 70 to 170 ppm, optionally 70 to 180 ppm, optionally 70 to 180 ppm, optionally 70 to 190 ppm, optionally 70 to 200 ppm, optionally 60 to 200 ppm, and optionally 50 to 200 ppm.

[0070] In some embodiments, the volume average particle diameter D of the silicon-based negative electrode active material v50 is 4 μm to 10 μm, and selectively 5 μm to 8 μm. In the above embodiment, the silicon-based anode active material has improved cycle performance and rate performance.

[0071] In some embodiments, the volume-average particle size D of the silicon-based negative electrode active material v 50 is selectively 4 μm or larger, and more selectively 5 μm or larger. This allows for a reduction in the film deposition consumption of active ions at the negative electrode and a reduction in side reactions of the electrolyte at the negative electrode, thereby reducing the irreversible capacity of the secondary battery, improving the cycle performance of the secondary battery, and reducing the amount of adhesive added to the negative electrode sheet, which is advantageous for increasing the energy density of the secondary battery. Average particle size D v The particle size 50 is selectively 10 μm or less, and more selectively 8 μm or less. This shortens the migration path of active ions and electrons within the material particles, increasing the ion and electron migration rate, which is advantageous for improving the kinetic performance of secondary batteries, preventing the silicon-based negative electrode active material from breaking down during the charging and discharging process, and ultimately improving the cycle performance of secondary batteries.

[0072] In some embodiments, the specific surface area of ​​the silicon-based negative electrode active material is 6 m². 2 / g or less, selectively 2m 2 / g~5m 2 The value is / g. In the above embodiment, the silicon-based anode active material has further improved cycle performance and rate performance.

[0073] In some embodiments, the specific surface area of ​​the silicon-based negative electrode active material is 2m². 2 / g~6m 2 The specific surface area is selectively 2 m². 2 A specific surface area of ​​6 m² or more allows for an increased number of active sites on the surface of the material particles, effectively enhancing the electrochemical performance of the silicon-based negative electrode active material and meeting the requirements for the dynamic performance of secondary batteries. 2Having a value of less than / g is advantageous in reducing side reactions at the negative electrode of the electrolyte, and by reducing the consumption of active ions for film formation at the negative electrode, it is possible to reduce the irreversible capacity of the secondary battery and improve the cycle performance of the secondary battery.

[0074] In some embodiments, the powder volume resistivity of the silicon-based anode active material at a pressure of 4 MPa is 6 Ω·cm or less, and selectively between 0.5 Ω·cm and 4.5 Ω·cm. In the above embodiments, the silicon-based anode active material has further improved rate performance.

[0075] In some embodiments, the powder volume resistivity of the silicon-based anode active material at a pressure of 4 MPa is 6 Ω·cm or less, and more selectively 4.5 Ω·cm or less. Having the powder volume resistivity of the silicon-based anode active material within this range reduces the inhibition of electron movement within the particles, which is advantageous for improving the kinetic performance of the silicon-based anode active material.

[0076] In some embodiments, the press density of the silicon-based anode active material at a pressure of 49,000 N is 1.4 to 1.8 g / cm³. 3 Therefore, selectively, 1.5-1.7 g / cm³ is preferred. 3 In the above embodiment, the battery has an even more improved energy density.

[0077] In some embodiments, the silicon-based negative electrode material contains Si and O elements, and the molar ratio of O to Si elements is greater than 0 and less than 2, selectively 0.2 to 1.8:1, more selectively 0.3 to 1.7:1, more selectively 0.4 to 1.6:1, more selectively 0.6 to 1.5:1, more selectively 0.7 to 1.4:1, more selectively 0.8 to 1.3:1, more selectively 0.9 to 1.2:1, and more selectively 1.0 to 1.1:1.

[0078] In some embodiments, at least a portion of the surface of the silicon-based negative electrode active material is covered with a coating layer.

[0079] In some embodiments, the coating layer material comprises one or more polymers, carbon materials, metallic materials, and metallic compounds. For example, the coating layer comprises one or more polymer coating layers, carbon coating layers, and metallic compound coating layers. Optionally, the polymer may be one or more selected from polyaniline, polyacetylene, polystyrene, polyacrylonitrile, polyvinyl chloride, and polyethylene. Optionally, the carbon material may comprise one or more graphite, mesocarbon microbeads (MCMB), hydrocarbon compound pyrolysis carbon, hard carbon, and soft carbon, where graphite may comprise one or more natural graphite and artificial graphite. Optionally, the metallic compound may comprise one or more Ti5Si3, Al2O3, and TiO2. The coating layer further mitigates the volume expansion effect of the silicon-based anode active material, thereby extending the cycle life of the material. On the other hand, the coating layer further protects the silicon-based negative electrode active material, suppressing side reactions of the electrolyte on the material surface and protecting the material surface from corrosion by the electrolyte. This allows the silicon-based negative electrode active material to exhibit high capacity, thereby further extending the battery's cycle life.

[0080] In the second aspect, the present application is: To provide a raw material containing Si element, O element, K element, P element and alkaline earth metal element, The vapor deposition method employs a method in which the raw material is heated to form vapor, and then the vapor is cooled to form a deposited material. The present invention provides a method for preparing a silicon-based negative electrode active material according to any one of the above items, comprising: pulverizing a deposited material and obtaining a pulverization product.

[0081] In some embodiments, the method for preparing silicon-based negative electrode active material is as follows: The process further includes applying a coating treatment to the pulverized product to obtain a product with a coated layer.

[0082] In some embodiments, the Si element in the raw material may be derived from elemental silicon and silicon oxide, and the O element in the raw material may be derived from silicon oxide. Here, elemental silicon includes, for example, metallic silicon. Silicon oxide includes, for example, one or more of silicon monoxide (SiO) and silicon dioxide (SiO2). The purity of elemental silicon is, for example, 3N or higher, 4N or higher, 5N or higher, or 6N or higher.

[0083] In some embodiments, the potassium element in the raw material may come from elemental silicon or silicon oxide itself, or from a potassium source added to the raw material.

[0084] In some embodiments, the phosphorus element in the raw material may come from elemental silicon or silicon oxide itself, or from a phosphorus source added to the raw material.

[0085] In some embodiments, the alkaline earth metal elements in the raw materials may come from elemental silicon or the silicon oxide itself, or from an alkaline earth metal source added to the raw materials.

[0086] In some embodiments, the potassium source may be one or more selected from potassium oxides, potassium hydroxide, potassium chloride, and potassium silicate.

[0087] In some embodiments, the phosphorus source may be one or more selected from elemental phosphorus, phosphorus oxides, and phosphates.

[0088] In some embodiments, the alkaline earth metal source may be one or more selected from alkaline earth metals, alkaline earth metal alloys, and alkaline earth metal compounds, where the alkaline earth metal compound may be one or more selected from alkaline earth metal oxides, alkaline earth metal sulfides, alkaline earth metal carbonates, alkaline earth metal hydroxides, alkaline earth metal acetates, alkaline earth metal oxalates, alkaline earth metal nitrates, and alkaline earth metal sulfates.

[0089] In some embodiments, the raw material containing Si, O, K, P, and alkaline earth metal elements includes elemental silicon, silicon dioxide, a potassium source, a phosphorus source, and an alkaline earth metal source.

[0090] In some embodiments, the content of element K in the negative electrode active material is adjusted by adjusting the type and amount of potassium source in the raw materials.

[0091] In some embodiments, the content of element P in the negative electrode active material is adjusted by one or more means, such as mixing silicon oxide powders or metallic silicon powders with multiple P content, and adjusting the type and amount of phosphorus source.

[0092] In some embodiments, the operation of heating the raw materials to form steam is carried out in an inert atmosphere at atmospheric pressure or reduced pressure.

[0093] In some embodiments, the operation of cooling the vapor to form the deposited material is carried out in an inert atmosphere at atmospheric pressure or reduced pressure.

[0094] In the above preparation method, the inert atmosphere may be a nitrogen gas atmosphere, an argon gas atmosphere, a helium gas atmosphere, or the like. Selectively, the absolute pressure of the inert atmosphere is normal pressure (one standard atmospheric pressure) or reduced pressure (less than one standard atmospheric pressure). Selectively, the absolute pressure of the inert atmosphere is 10 Pa to 950 Pa, and more selectively, 20 Pa to 100 Pa.

[0095] In some embodiments, within the range of the inert atmosphere pressure described above, the content of K and P elements in the final silicon-based anode active material can be increased by lowering the pressure (i.e., increasing the vacuum).

[0096] In some embodiments, the heating temperature in the operation of heating the raw material to form steam is 1100 to 1550°C.

[0097] In some embodiments, the cooling temperature in the operation of cooling the vapor to form a deposited material is 700 to 900°C.

[0098] In some embodiments, by adjusting the cooling temperature during the operation of cooling the vapor to form a deposited material, the deposited material can obtain a suitable crystalline structure. Selectively, the cooling temperature is 850°C to 1050°C, which is advantageous for the silicon-based anode active material to obtain a good crystallite size and appropriate crystallinity, thereby having high cycle performance and performance. If the cooling temperature is lower than 800°C, the crystallinity of the material may be too low, potentially affecting the material's cycle performance, and if the cooling temperature is higher than 1050°C, the crystallite size of the material may be too large, potentially affecting the material's cycle performance.

[0099] In some embodiments, within the above heating temperature range, increasing the temperature can correspondingly increase the content of K and P elements in the final silicon-based anode active material.

[0100] In some embodiments, within the range of the inert atmosphere pressure described above, the content of K and P elements in the final silicon-based anode active material can be increased by lowering the pressure, i.e., increasing the vacuum level.

[0101] In some embodiments, the operation of crushing the deposited material includes performing coarse crushing-fine crushing-sorting operations on the deposited material based on predetermined parameters of volume-average particle size (Dv50) and specific surface area of ​​the product, in order to obtain a product that meets the predetermined parameters. In some embodiments, crushing and sorting treatment of the deposited material may be performed using any method known in the art and equipment such as a grinder or a jet crushing-sorting combination machine.

[0102] In some embodiments, a method for preparing a silicon-based anode active material further includes a coating treatment of the pulverized product to obtain a product with a coated layer.

[0103] In some embodiments, the coating layer material comprises one or more polymers, carbon materials, metallic materials, and metallic compounds. For example, the coating layer comprises one or more polymer coating layers, carbon coating layers, and metallic compound coating layers. Optionally, the polymer may be one or more selected from polyaniline, polyacetylene, polystyrene, polyacrylonitrile, polyvinyl chloride, and polyethylene. Optionally, the carbon material may comprise one or more graphite, mesocarbon microbeads (MCMB), hydrocarbon compound pyrolysis carbon, hard carbon, and soft carbon, where graphite may comprise one or more natural graphite and artificial graphite. Optionally, the metallic compound may comprise one or more Ti5Si3, Al2O3, and TiO2. The coating layer further mitigates the volume expansion effect of the silicon-based anode active material, thereby extending the cycle life of the material. On the other hand, the coating layer further protects the silicon-based negative electrode active material, suppressing side reactions of the electrolyte on the material surface and protecting the material surface from corrosion by the electrolyte. This allows the silicon-based negative electrode active material to exhibit high capacity, thereby further extending the battery's cycle life.

[0104] In some embodiments, a liquid-phase coating method is employed to coat the surface of the silicon-based anode active material and form a coating layer. For example, a polymer is dissolved in a certain solvent, thoroughly stirred with the silicon-based anode active material particles to ensure uniform mixing, and then the solvent is evaporated and removed, thereby uniformly coating the surface of the silicon-based anode active material particles with the polymer.

[0105] In some embodiments, a chemical vapor deposition method is used to coat the surface of the silicon-based anode active material, forming a coating layer. For example, by introducing a hydrocarbon compound gas into a reaction furnace containing the silicon-based anode active material and performing heat treatment in an inert atmosphere, the hydrocarbon compound is carbonized, forming a coating layer that covers the surface of the silicon-based anode active material, thereby obtaining a silicon-based anode active material with a coating layer covering its surface.

[0106] In some embodiments, the coating treatment includes a carbon coating treatment. Optionally, the carbon coating treatment includes placing the pulverized product in a chamber containing a carbon source gas, heating it to 700-1000°C, and maintaining the temperature for 1-6 hours.

[0107] In some embodiments, the coating treatment includes a carbon coating treatment. Optionally, the carbon coating treatment includes placing the pulverized product in a chamber containing a carbon source gas, heating it to 800-900°C, and maintaining the temperature for 2-5 hours.

[0108] In some embodiments, the alkaline earth metal source may be one or more of the following: elemental alkaline earth metal, alkaline earth metal hydroxide, alkaline earth metal carbonate, alkaline earth metal nitrate, amination alkaline earth metal, or hydride alkaline earth metal.

[0109] In some embodiments, the alkaline earth metal source may be one or more of metallic magnesium, magnesium hydroxide, magnesium carbonate, magnesium nitrate, aminomagnesium, and magnesium hydride.

[0110] As an example, the negative electrode current collector has two opposing surfaces in the thickness direction of itself, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.

[0111] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer material substrate (for example, a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE)).

[0112] In some embodiments, the negative electrode film layer may include silicon-based negative electrode active materials other than those known in the art and selected by those skilled in the art according to their actual needs. Examples include, but are not limited to, artificial graphite, natural graphite, hard carbon, soft carbon, one or more other silicon-based materials and tin-based materials. The other silicon-based materials may include one or more elemental silicon, silicon composites other than those of the present invention, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based materials may include one or more elemental tin, stannic acid compounds, and tin alloys. All of these materials are commercially available.

[0113] In some embodiments, the negative electrode film layer may further optionally include an adhesive. For example, the adhesive may be at least one selected from styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0114] In some embodiments, the negative electrode film layer may further optionally contain a conductive agent. For example, the conductive agent may be at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0115] In some embodiments, the negative electrode film layer may further optionally contain other additives, such as thickeners (e.g., sodium carboxymethylcellulose (CMC-Na)).

[0116] In some embodiments, the negative electrode sheet may be prepared in the following form. Components for preparing the above-mentioned negative electrode sheet, such as a silicon-based negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry. The negative electrode slurry is applied to a negative electrode current collector, and after processes such as drying and cold pressing, a negative electrode sheet can be obtained.

[0117] [Positive electrode sheet] In some embodiments, the positive electrode sheet typically includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a positive electrode active material.

[0118] As an example, the positive electrode current collector has two opposing surfaces in the thickness direction of itself, and the positive electrode film layer is provided on either one or both of the two opposing surfaces of the positive electrode current collector.

[0119] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy) on a polymer material substrate (for example, a substrate such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), or polyethylene (PE)).

[0120] In some embodiments, the positive electrode film layer may further optionally include an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0121] In some embodiments, the cathode film layer may further optionally contain a conductive agent. For example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0122] In some embodiments, the positive electrode sheet may be prepared in the following form. Components for preparing the above-mentioned positive electrode sheet, such as a positive electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry. The positive electrode slurry is applied to a positive electrode current collector, and after processes such as drying and cold pressing, a positive electrode sheet can be obtained.

[0123] [Cathode active material] In some embodiments, the positive electrode active material may be a positive electrode active material used in secondary batteries that are well known in the art.

[0124] As an example, the positive electrode active material may include at least one of olivine-structured lithium-containing phosphates, lithium transition metal oxides, and modified compounds of each. However, this application is not limited to these materials, and other conventional materials usable as battery positive electrode active materials may be used. These positive electrode active materials may be used individually or in combination of two or more. Here, examples of lithium transition metal oxides include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, and lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM 333 (It may also be abbreviated as LiNi) 0.5 Co 0.2 Mn 0.3 O2(NCM 523 (It may also be abbreviated as LiNi) 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (It may also be abbreviated as LiNi) 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (It may also be abbreviated as LiNi) 0.8 Co 0.1 Mn 0.1 O2(NCM 811 (May be abbreviated as LiNi) Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05The olivine structure lithium-containing phosphate may include, but is not limited to, at least one of the following: O2) and its modified compounds. Examples of lithium-containing phosphates with an olivine structure may include, but is not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), lithium iron phosphate and carbon composite materials, lithium manganese phosphate (e.g., LiMnPO4), lithium manganese phosphate and carbon composite materials, lithium iron manganese phosphate, and lithium iron manganese phosphate and carbon composite materials.

[0125] [Electrolyte] The electrolyte acts to conduct ions between the positive electrode sheet and the negative electrode sheet. This application does not specifically limit the type of electrolyte, and it may be selected according to the needs. For example, the electrolyte may be in a liquid state, a gel state, or a completely solid state.

[0126] In some embodiments, the electrolyte is in a liquid state and comprises an electrolyte salt and a solvent.

[0127] In some embodiments, the electrolyte salt is selected from sodium perchlorate, sodium hexafluoride phosphate, sodium tetrafluoroborate, and sodium hexafluoride arsenate.

[0128] In some embodiments, the solvent may be at least one selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0129] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain aspects of the battery's performance, such as additives that improve battery overcharge performance, or additives that improve battery high-temperature or low-temperature performance.

[0130] [Separator] In some embodiments, the secondary battery further includes a separator. The present application does not particularly limit the type of separator, and any well-known porous separator having good chemical and mechanical stability may be selected.

[0131] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single-layer thin film or a multilayer composite thin film, and is not particularly limited. If the separator is a multilayer composite thin film, the materials of each layer may be the same or different, and is not particularly limited.

[0132] In some embodiments, the positive electrode sheet, negative electrode sheet, and separator may be manufactured as an electrode assembly by a winding process or a lamination process.

[0133] In some embodiments, the secondary battery may include an outer casing. This casing may be used to seal the electrode assembly and electrolyte.

[0134] In some embodiments, the casing of the secondary battery may be a rigid shell, such as a rigid plastic shell, an aluminum shell, or a steel shell. The casing of the secondary battery may also be a flexible package, such as a bag-type flexible package. The material of the flexible package may be plastic, and examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0135] This application does not particularly limit the shape of the secondary battery, and it may be cylindrical, rectangular, or any other shape. For example, Figure 1 shows a rectangular secondary battery 5 as one example.

[0136] In some embodiments, referring to Figure 2, the exterior may include a housing 51 and a cover plate 53. Here, the housing 51 may include a bottom plate and side plates connected to the bottom plate, the bottom plate and side plates enclosing each other to form a housing chamber. The housing 51 has an opening that communicates with the housing chamber, and the cover plate 53 can cover the opening to close the housing chamber. The positive electrode sheet, negative electrode sheet and separator can be formed into an electrode assembly 52 by a winding process or a lamination process. The electrode assembly 52 is sealed inside the housing chamber. The electrolyte is impregnated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be selected by those skilled in the art according to their specific practical needs.

[0137] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, and the specific number may be selected by those skilled in the art depending on the application and capacity of the battery module.

[0138] Figure 3 shows a battery module 4 as one example. Referring to Figure 3, in the battery module 4, a plurality of secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, they may be arranged according to any other configuration. Furthermore, the plurality of secondary batteries 5 may be fixed via fasteners.

[0139] Optionally, the battery module 4 may further include an outer casing having a housing space, in which a plurality of secondary batteries 5 are housed.

[0140] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by those skilled in the art depending on the application and capacity of the battery pack.

[0141] Figures 4 and 5 show a battery pack 1 as an example. Referring to Figures 4 and 5, the battery pack 1 may include a battery case and a plurality of battery modules 4 provided in the battery case. The battery case includes an upper casing 2 and a lower casing 3, the upper casing 2 can cover the lower casing 3 and form a closed space for housing the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case according to any configuration.

[0142] Furthermore, the present application provides an electrical device comprising at least one of a secondary battery, battery module, or battery pack relating to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0143] As the aforementioned electrical device, a secondary battery, battery module, or battery pack may be selected depending on the usage needs.

[0144] Figure 6 shows an example of an electrical device. This electrical device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density needs of the secondary battery in this electrical device, a battery pack or battery module may be employed.

[0145] The embodiments of this application are described below. The embodiments described below are illustrative and are intended solely for interpretation purposes and should not be understood as limiting this application. Note that Example E14 is for reference only.If specific techniques or conditions are not specified in the examples, the procedures shall be carried out in accordance with the techniques or conditions described in the literature within this art, or in accordance with the product instructions. If the manufacturer of the reagents or equipment used is not specified, they shall all be common products that are commercially available.

[0146] 1. Method for preparing silicon-based negative electrode active material 1.1 Overview In the following specific embodiments, the general outline of the method for preparing the silicon-based anode active material is as follows. 1) Provide a vapor containing Si, O, K, P, and Mg elements, and cool the vapor to obtain a deposited material. 2) The deposited material is pulverized to obtain the pulverization product. 3) The pulverized product is subjected to carbon coating treatment to obtain a carbon-coated product.

[0147] 1.2 Details In the following specific embodiments, a detailed explanation of the method for preparing the silicon-based anode active material is provided below. 1) Provide a raw material composition containing elemental silicon, silicon oxide, potassium source (K2CO3), phosphorus source (P2O5), and Mg source (metallic magnesium) according to the content of Si, O, K, P, and Mg elements in the target product. 2) Using a vapor deposition method in a helium gas atmosphere with an absolute pressure of 30 Pa, the raw material composition is heated to 1300°C to form vapor, and then the vapor is cooled to 900°C to form the deposited material. 3) Collect the deposited material and grind it into a powder. 4) Place the powder in the reaction chamber of the vapor deposition apparatus, pass a mixed gas of carbon source gas (acetylene) and nitrogen gas in a ratio of 20% by volume through the reaction chamber, heat to 750°C, maintain for 2 hours, and obtain a carbon-coated product. 5) The carbon-coated product and the lithium source (lithium amination) are mixed according to a mass ratio of 100:30, heated to 650°C, kept warm for 2 hours to carry out the lithiation reaction, and the product is collected to obtain the negative electrode active material.

[0148] In the above preparation method, silicon-based anode active materials with various K and P content can be obtained simply by appropriately adjusting the content of alkaline earth metal sources, potassium sources, and phosphorus sources in the raw material mixture based on the composition of the target product. However, it should be understood that if certain amounts of K and P elements are already present in some elemental silicon and silicon dioxide due to the influence of the purity of elemental silicon and silicon dioxide, it is necessary to appropriately adjust the content of potassium sources and phosphorus sources in the raw material mixture according to the component composition of the target product of the sample.

[0149] According to the method described above, several types of silicon-based negative electrode active material samples (hereinafter referred to as "samples") are obtained, and these samples have different K and P content. These samples have the following properties. 1) The silicon-based anode active material is a silicon-based anode active material having a carbon coating layer, where the carbon coating layer content is 4.2±1%, and the remainder is the silicon-based anode active material. 2) The molar ratio of O element to Si element in the silicon-based negative electrode active material is 1 ± 0.1:1. 3) Based on 100% silicon-based negative electrode active material, the Mg element content is 7±0.5%. 4) Based on 100% silicon-based negative electrode active material, the K content is as shown in Table 1. 5) Based on 100% silicon-based negative electrode active material, the P content is as shown in Table 1. 6) The volume-average particle size Dv50 of the silicon-based anode active material is 6.0 ± 1 μm. 7) The specific surface area of ​​the silicon-based anode active material is 5 ± 0.25 m². 2 It is / g. 8) The powder volume resistivity of the silicon-based anode active material at a pressure of 4 MPa is 4.2 ± 0.25 Ω·cm. 9) The press density of the silicon-based anode active material at a pressure of 49,000 N is 1.6 ± 0.1 g / cm³. 3 That is 10) The silicon-based negative electrode active material contains MgSiO3, and the MgSiO3 has a half-peak width of 0.5°±0.1° in its XRD diffraction peak and a grain size of 16±1 nm.

[0150] Table 1 shows silicon-based anode active material samples with different K and P content.

[0151] Preparation of coin-type batteries (1) Preparation of the negative electrode sheet: The silicon-based negative electrode active material prepared above, the conductive agent Super-P (conductive carbon black), and the adhesive PAA (polyacrylic acid) are thoroughly mixed in an appropriate amount of deionized water in a mass ratio of 85:5:10 to form a uniform negative electrode slurry. The negative electrode slurry is then applied to the surface of the copper foil of the negative electrode current collector, and after drying and cold pressing, a negative electrode sheet is obtained. (2) Counter electrode: Metallic lithium sheet. (3) Separator: Polyethylene (PE) thin film. (4) Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1. Then, LiPF6 is uniformly dissolved in the above solution to obtain the electrolyte, and fluoroethylene carbonate (FEC) is added. Here, the concentration of LiPF6 is 1 mol / L, and the mass percentage of FEC in the electrolyte is 6%. (5) Preparation of coin-type battery: The negative electrode sheet, separator, and metallic lithium sheet counter electrode are stacked in order, and the electrolyte is added to obtain a coin-type battery.

[0152] 2. Analysis and detection methods 2.1 Elemental analysis (e.g., K, P, Si, and alkaline earth metal elements) Elemental content is a well-known term in this field, and it may be measured using methods known in this field. After decomposing the silicon-based anode active material by referring to EPA-3052-1996 "Microwave-assisted acid decomposition of silicates," the content of the target element may be measured using an ICAP-7000 type inductively coupled plasma atomic emission spectrometer (ICP-OES) from Thermo Fisher Scientific, USA, in accordance with EPA 6010D-2014 "Inductively coupled plasma atomic emission spectroscopy." The specific measurement method is as follows: A 0.5 g sample of silicon-based anode active material is microwave-decomposed using 10 mL of nitric acid and 10 mL of hydrofluoric acid. After decomposition, the sample is placed in a 50 mL volumetric flask and brought to a constant volume. Then, the content of the target element is measured using an ICAP-7000 type ICP-OES.

[0153] 2.2 Elemental Analysis (Oxygen, Carbon) Elemental content has a meaning well known in this field, and it may be measured using methods known in this field. The carbon element content in silicon-based anode active material may be measured by referring to GB / T 20123-2006 / ISO 15350:2000, and the measuring instrument may be an HCS-140 type infrared carbon-sulfur analyzer.

[0154] The oxygen element content may be determined by referring to JY / T 017-1996 General Rules for Elemental Analysis Methods, and the measuring instrument may be an Elementar Rapid OXY Cube oxygen element analyzer.

[0155] 2.3 Volume resistivity The volume resistivity of a material is a well-known term in this field, and it may be measured using instruments and methods well-known in this field. For example, the four-probe method may be used to measure the powder volume resistivity of the silicon-based anode active material of this application at a pressure of 4 MPa. The measurement method includes placing the silicon-based anode active material powder of this application onto a sample stage, applying a pressure of 4 MPa to the powder using a press, and after the pressure stabilizes, reading the powder volume resistivity of the silicon-based anode active material at a pressure of 4 MPa using a resistivity meter.

[0156] 2.4 Press density The press density of the material has a meaning that is well known in this field, and may be measured using instruments and methods well known in this field, for example, referring to the GB / T24533-2009 standard, and may be performed using an electronic pressure tester such as an electronic pressure tester of type UTM7305. A sample of approximately 1 g is weighed accurately, with a base area of ​​1.327 cm². 2 By placing the sample in a mold, applying a pressure of 49,000 N using a pressurizing device, maintaining this pressure for 30 seconds, then releasing the pressure, and subsequently measuring the height of the sample, the press density of the material can be obtained using the formula ρ = m / (1.327 × h). In the formula, ρ represents the press density of the material, m represents the mass of the sample, and h represents the height of the sample after the pressure of 49,000 N has been applied, maintained for 30 seconds, and then released.

[0157] 2.4, Powder particle size analysis The Dv10, Dv50, and Dv90 values ​​for materials are well-known in this field, and measurements may be taken using methods known in this field. For example, measurements may be taken using a laser particle size analyzer (e.g., Malvern Master Size 3000), referring to standard GB / T 19077-2016.

[0158] The physical definitions of Dv10, Dv50, and Dv90 are the particle sizes corresponding to the percentage of the cumulative volume distribution of the silicon-based anode active material reaching 10%, 50%, and 90%, respectively.

[0159] 2.5 Analysis of Specific Surface Area The specific surface area of ​​a material has a meaning that is well known in this field, and it may be measured using instruments and methods well known in this field. For example, it may be measured by referring to the GB / T 19587-2017 standard for measuring the specific surface area of ​​solid materials by gas adsorption BET method, employing the nitrogen gas adsorption specific surface area analysis measurement method, and calculated using the BET (Brunauer Emmett Teller) method. Here, the nitrogen gas adsorption specific surface area analysis measurement may be performed using a Tri StarII 3020 type specific surface area pore size analyzer from Micromeritics, Inc., USA.

[0160] 2.6. Battery Performance Measurement (1) Cycle performance At 25°C and normal pressure, a coin-type battery is discharged to 0.005V with a constant current of 0.1C, then discharged again to 0.005V with a constant current of 0.04C, and left to stand for 5 minutes. The discharge capacity at this time, i.e., the lithium insertion capacity for the first cycle, is recorded. Subsequently, the battery is charged to 1.5V with a constant current of 0.1C, and left to stand for 5 minutes. This constitutes one charge-discharge cycle, and the charge capacity at this time, i.e., the lithium desorption capacity for the first cycle, is recorded. The coin-type battery is subjected to 30 cycle charge-discharge measurements according to the above method, and the lithium desorption capacity for each measurement is recorded. Cycle capacity retention rate (%) = Reversible lithium desorption capacity at cycle 1 / Reversible lithium desorption capacity at cycle 500 × 100%

[0161] (2) 4C discharge rate measurement At 25°C and normal pressure, a coin-type battery is discharged to 0.005V with a constant current at a rate of 0.1C, then discharged to 0.005V with a constant current at 0.04C, then left to stand for 5 minutes, and subsequently charged to 1.5V with a constant current at a rate of 0.1C, then left to stand for 5 minutes. This constitutes one charge-discharge cycle. The same flow is used, but the charge and discharge currents are changed. Charge and discharge are performed at currents of 0.1C, 0.33C, 1C, 2C, and 4C, and the discharge capacity is recorded after 10 cycles for each current. 4C discharge capacity retention rate (%) = Average 4C lithium desorption capacity / Average 0.1C lithium desorption capacity × 100%

[0162] [Table 1]

[0163] III. Results and Review Table 1 shows the raw materials and composition of silicon-based anode active materials in several embodiments of the present application, the content and weight ratio of K and P elements in the silicon-based anode active material product, and the battery performance based on using the above silicon-based anode active material. Each of these will be examined below.

[0164] (1) Composition of raw materials The raw material silicon used in samples (E1~E14) is metallic silicon 1 (Si≧99wt%, K=100ppm, P=30ppm).

[0165] The raw material silicon used in samples (D1-D3) is metallic silicon 2 (Si ≥ 99.9 wt%, without K and P).

[0166] As can be seen from Table 2, the K and P elements in the silicon-based negative electrode active material may come from multiple sources. a) The element K in the silicon-based negative electrode active material may be derived from the raw material metal silicon. b) The element P in the silicon-based negative electrode active material may be derived from the raw material metal silicon. c) The potassium element in the silicon-based negative electrode active material may be derived from an added potassium source. d) The phosphorus element in the silicon-based negative electrode active material may be derived from an additional phosphorus source.

[0167] Those skilled in the art can adaptively adjust the content of phosphorus (P) and potassium (K) elements in the raw materials based on the target chemical composition of the silicon-based anode active material, and ultimately obtain an anode active material having the target chemical composition. If it is necessary to increase / decrease the content of potassium in the target anode active material, metallic silicon (or silicon oxide) with a higher / lower content of potassium may be used, and the amount of additional potassium source added to the raw materials may be increased / decreased. If it is necessary to increase / decrease the content of phosphorus (P) in the target anode active material, metallic silicon (or silicon oxide) with a higher / lower content of phosphorus may be used, and the amount of additional phosphorus source added to the raw materials may be increased / decreased.

[0168] (2) Synergistic effect between K element and P element The following is a detailed analysis of Comparative Examples D1, D2, and D3 in relation to Example E2. In the silicon oxide composite of Comparative Example D3, neither K nor P elements were present, and its 4C capacity retention rate was 41.0%. In the silicon oxide composite of Comparative Example D1, 1200 ppm of K element was present, but no P element was present, and its 4C capacity retention rate was 46.1%, an increase of only 12% compared to D3. In the silicon oxide composite of Comparative Example D2, 90 ppm of P element was present, but no K element was present, and its 4C capacity retention rate was 45.5%, an increase of only 11% compared to D3. In the silicon oxide-based composite of Example E2, 1249 ppm of K and 90 ppm of P were simultaneously contained, and its 4C capacity retention value was 57%, which is a 39% increase compared to D3. This increase is far greater than the simple summation of performance improvements from the addition of K or P alone (i.e., 12% + 11% = 33%). Therefore, the above experimental evidence demonstrates a synergistic effect beyond expectations that was definitely brought about by the bonding of K and P.

[0169] (3) Weight ratio of K / P in silicon oxide composites The experimental data in Table 1 demonstrates that when the K / P weight ratio is greater than 1, the performance of the negative electrode active material is significantly improved.

[0170] In Example E14, the K / P weight ratio was 0.8:1 (<1), the anode active material had a 4C capacity retention rate of 48.8%, and the cycle performance was 78.6%. In Examples E1 to E13, the K / P weight ratio ranged from 7.7:1 to 14.8:1 (greater than 1), the anode active material had a 4C capacity retention rate of 50% to 67%, and the capacity retention rate was 73% to 78%, which is superior to Example E14.

[0171] The experimental data above explains that when the K content in the silicon oxide composite is greater than the P content, the silicon oxide composite exhibits a more significant improvement in cycle performance and rate performance.

[0172] (4) Regarding the K / P ratio in silicon oxide composites As shown in Examples E4 to E13, when the K / P weight ratio is 7.7:1 to 14.8:1, the negative electrode active material exhibits a 4C capacity retention value of 50% to 67%, representing further improvements in cycle performance and rate performance.

[0173] As shown in Examples E9 to E11, when the K / P weight ratio is 9.2:1 to 10.3:1, the negative electrode active material exhibits a 4C capacity retention rate of 64.5% to 67.4%, representing further improvements in cycle performance and rate performance.

[0174] (5) Regarding the content of element K and element P in silicon oxide composites As shown in Examples E1 to E14, the K element content in the silicon oxide composite is 600 ppm or more, for example, 800 ppm to 1500 ppm, and the negative electrode active material exhibits improved cycle performance and rate performance.

[0175] As shown in Examples E1 to E14, the content of element P in the silicon oxide composite is 1000 ppm or less, for example, between 50 ppm and 1000 ppm. The negative electrode active material exhibits improved cycle performance and rate performance.

[0176] As shown in Examples E1 to E13, the content of element K in the silicon oxide composite is 1000 ppm or more, for example, 1000 ppm to 1500 ppm, and the negative electrode active material exhibits improved cycle performance and rate performance.

[0177] As shown in Examples E1 to E13, the content of element P in the silicon oxide composite is 500 ppm or less, for example, 50 ppm to 200 ppm. The negative electrode active material exhibits improved cycle performance and rate performance.

[0178] The experimental data above explains that when silicon oxide composites contain either P or K elements alone, the cycle performance and rate performance are usually improved in only one of them, and the improvement is not significant. However, when silicon oxide composites contain a combination of K and P elements, the negative electrode active material shows improvements in both cycle performance and rate performance, and the improvement is particularly significant. This explains that the K and P elements acquire a synergistic effect greater than expected.

[0179] Furthermore, this application is not limited to the embodiments described above. The embodiments described above are merely illustrative, and any embodiment having substantially the same configuration as the technical concept and achieving the same effects within the scope of the technical aspects of this application is included within the scope of the technical aspects of this application. In addition, other forms constructed by adding various modifications to the embodiments that a person skilled in the art could conceive of, or by combining some of the components of the embodiments, are also included within the scope of this application, as long as they do not depart from the spirit of this application.

Claims

1. A silicon-based negative electrode active material, It contains alkaline earth metal element-containing silicates and simultaneously contains K and P elements. The K / P mass ratio is between 7 and 15. Silicon-based negative electrode active material.

2. The K / P mass ratio is 9 to 15. The silicon-based negative electrode active material according to claim 1.

3. The content of element K is 600 ppm or more. The silicon-based negative electrode active material according to claim 1.

4. The content of element P is 500 ppm or less. The silicon-based negative electrode active material according to claim 1.

5. (1) Volume average particle size D v 50 is between 4 μm and 10 μm. (2) The specific surface area is 6 m 2 It must be less than or equal to / g. (3) The volume resistivity of the powder at a pressure of 4 MPa shall be 6 Ω·cm or less. (4) The press density at a pressure of 49,000 N is 1.4 to 1.8 g / cm³. 3 Being (5) The alkaline earth metal element-containing silicate contains a magnesium-containing silicate, and the half-peak width of the XRD diffraction peak of the magnesium-containing silicate is 0.65° or less. (6) The alkaline earth metal element-containing silicate contains a magnesium-containing silicate, and the crystal grain size of the magnesium-containing silicate is 12 nm or larger, one or more of these characteristics. The silicon-based negative electrode active material according to claim 1.

6. At least some of the surfaces have a coating layer, The silicon-based negative electrode active material according to claim 1.

7. - To provide raw materials containing Si element, O element, K element, P element and alkaline earth metal elements, - A vapor deposition method is employed, in which the raw material is heated to form vapor, and then the vapor is cooled to form the deposited material. This includes: pulverizing the deposited material and obtaining the pulverization product, A method for preparing a silicon-based negative electrode active material according to claim 1.

8. The process further includes applying a coating treatment to the pulverized product to obtain a product with a coating layer. The method according to claim 7.

9. (1) In the operation of heating the raw material to form steam, the heating temperature shall be 1100 to 1550°C. (2) In the operation of cooling the vapor to form a deposited material, the cooling temperature is 700 to 900°C, and has one or more of these characteristics. The method according to claim 7.

10. A negative electrode comprising a silicon-based negative electrode active material according to any one of claims 1 to 6, Secondary battery.

11. A secondary battery as described in claim 10, Electrical device.

Citation Information

Patent Citations

  • Porous carbon material, its manufacturing process and adsorbent, mask, adsorption sheet, and supporting member

    JP2008273816A

  • Negative electrode material for secondary cell for nonaqueous electrolytic solution, process for the production thereof, and secondary cell for nonaqueous electrolytic solution using it

    WO1996027911A1

  • Negative electrode active material for secondary batteries, and secondary battery

    WO2020045257A1